Current concepts of photosensitivity in cutaneous lupus erythematosus - Klein, Benjamin; Kunz, Manfred (Frontiers in Medicine, 2022)
Cutaneous lupus erythematosus (CLE) represents a complex autoimmune disease with a broad phenotypic spectrum ranging from acute to chronic destructive cutaneous lesions. Patients with CLE exhibit high photosensitivity and UV irradiation can lead to systemic flares in systemic lupus erythematosus. However, the exact mechanisms how UV irradiation enhances cutaneous inflammation in lupus are not fully understood. Recently, new molecular mechanisms of UV-driven immune responses in CLE were identified, offering potential therapeutic approaches. Especially the induction of type I interferons, central cytokines in lupus pathogenesis which are released by various skin cells, have become the focus of current research. In this review, we describe current pathogenic concepts of photosensitivity in lupus erythematosus, including UV-driven activation of intracellular nucleic acid sensors, cellular cytokine production and immune cell activation. Furthermore, we discuss activated pathways contributing to enhanced apoptosis as well as intracellular translocation of autoantigens thereby promoting CLE upon UV light exposure.